2023
DOI: 10.3847/2041-8213/acb54b
|View full text |Cite
|
Sign up to set email alerts
|

An X-Ray-dim “Isolated” Neutron Star in a Binary?

Abstract: We report the discovery of a dark companion to 2MASS J15274848+3536572 with an orbital period of 6.14 hr. Combining the radial velocity from LAMOST observations and modeling of the multiband light curve, one obtains a mass function of ≃0.131 M ⊙, an inclination of 45 .° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…such events are broad, with consequences for the heliosphere (Fields et al 2008; and possibly for the biosphere (Ruderman 1974;Hartmann et al 2002;Melott et al 2004Melott et al , 2019. Other astrophysical observables include searches for nearby neutron stars whose location and kinematics point to a Local Bubble origin (Tetzlaff et al 2010;Neuhäuser et al 2020;Lin et al 2023;Zheng et al 2022).…”
Section: Conclusion: Unearthing the Origin Of R-process Radioisotopesmentioning
confidence: 99%
“…such events are broad, with consequences for the heliosphere (Fields et al 2008; and possibly for the biosphere (Ruderman 1974;Hartmann et al 2002;Melott et al 2004Melott et al , 2019. Other astrophysical observables include searches for nearby neutron stars whose location and kinematics point to a Local Bubble origin (Tetzlaff et al 2010;Neuhäuser et al 2020;Lin et al 2023;Zheng et al 2022).…”
Section: Conclusion: Unearthing the Origin Of R-process Radioisotopesmentioning
confidence: 99%
“…It is premature to claim any stronger conclusion, although this is an important case and other detections could add to the whole picture. A recent work by Lin et al (2023) reports another candidate with M = 0.98 ± 0.03 M ⊙ that deserves attention in connection to the XMMU J173203.3-344518 case.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, it is of great interest to find the potential remnants, e.g., nearby NSs, of these events. Recent efforts in this regard include the studies of Zheng et al (2023) and Lin et al (2023). Zheng et al (2023) discovered an NS candidate, J2354, located approximately 128 pc away from the solar system, in which the unseen compact object has a mass of 1.4 ∼ 1.6 M e .…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al (2023) discovered an NS candidate, J2354, located approximately 128 pc away from the solar system, in which the unseen compact object has a mass of 1.4 ∼ 1.6 M e . In the work of Lin et al (2023), the authors claim to have identified a binary system, J1527, located 118 pc from the solar system, with an unseen NS candidate of approximately 0.98 M e .…”
Section: Introductionmentioning
confidence: 99%